The Model of Organizational Commitment and Work Satisfaction : Organizational Citizenship Behavior Perspective - Husainah, Nazifah; Wardana, Wikrama; Maria, Elvie; Hotman Malau, Jan; Sambarani, Budi; Sovitriana, Rilla; Cahyati, Peni (International Journal of Advanced Multidisciplinary, 2023)
The objective of this research is to analyze how Organizational Commitment and Work Satisfaction impact Organizational Citizenship Behavior. Using a quantitative research approach, the study analyzed data from 70 respondents across 20 manufacturing companies in West Java and processed it through the SEM-PLS methodology. The study findings suggest that Organizational Commitment and Work Satisfaction both have a direct influence on Organizational Citizenship Behavior in manufacturing companies located in West Java.